2017
DOI: 10.1186/s13104-017-2965-2
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic factors and availability of piped fountains affect food hygiene practice of food handlers in Bahir Dar Town, northwest Ethiopia: a cross-sectional study

Abstract: BackgroundMorbidity and mortality rates of food borne diseases are consistently highest in African due to poor food handling and sanitation practices. Thus, the study aimed to assess food handling practice and associated factors among food handlers of Restaurants in Bahir Dar Town, northwest, Ethiopia. A cross-sectional study was conducted from December, 7/2012 to January, 2/2013 among food handlers working in 106 restaurants in Bahir Dar Town. A structured questionnaire composed of socio-demographic factors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
37
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 11 publications
12
37
9
Order By: Relevance
“…In addition, the odds of performing good food handling practice among food handlers who had 6-10 years' experience were 2.43 time higher as compared to those who hadn't. This finding was consistent with the study in Bahirdar, which had revealed that food handlers who had greater than 2years work experience were 3.4 times likely to have good food handling practice [4]. Similarly, Gizaw et al (2014) had mentioned that food handlers who had 3years experience were 3.37 times likely to have good food handling practice [26].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In addition, the odds of performing good food handling practice among food handlers who had 6-10 years' experience were 2.43 time higher as compared to those who hadn't. This finding was consistent with the study in Bahirdar, which had revealed that food handlers who had greater than 2years work experience were 3.4 times likely to have good food handling practice [4]. Similarly, Gizaw et al (2014) had mentioned that food handlers who had 3years experience were 3.37 times likely to have good food handling practice [26].…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, food handlers who had attained education above grad twelve were 2.29 times more likely to have good food handling practices as compared to illiterates. This result was consistence with the study conducted in Bahirdar, which revealed that food handlers who had formal education were 6.4 times more likely to have good food handling practices [4]. This is because the depth of knowledge could affect food handler's food handling practices.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations